Pengembangan Pariwisata Perdesaan Oleh Dinas Pariwisata dan Kebudayaan di Kabupaten Pangandaran - Gian Ramadhan; Dini Yuliani; Asep Nurdin Rosihan Anwar (JOURNAL SAINS STUDENT RESEARCH, 2025)
This research is behind the lack of optimal development strategy for Rural Tourism Potential by the Pangandaran Regency Tourism and Culture Office. The research method used is descriptive with a qualitative approach. Data sources include primary data from 6 research informants as well as the results of field observations and secondary data from relevant documents, laws, research journals, and other references. Data collection techniques include interviews, observations and documentation as well as data analysis techniques consisting of data reduction, data presentation, conclusions. The results of the study show that the strategy for developing Rural Tourism Potential by the Pangandaran Regency Tourism and Culture Office. This is evidenced by several indicators that are not optimal, including job creation, gender equality in the tourism community, preservation of culture and arts, cultural awareness, cultural education, tourism waste management, concern for conservation, environmental carrying capacity, and participation of local populations. Obstacles are caused by the lack of local human resource capacity, especially in managerial, digital, and creative aspects; infrastructure inequality between tourist villages; lack of digital and cultural literacy among tourism actors, as well as weak cross-sector coordination between agencies, communities, and village governments. Efforts are made to improve training and empowerment, draft community regulations, encourage digital promotion, cooperation with universities and the private sector, and incorporate cross-sector programs such as Eco Tourism and indigenous peoples' protection.